INFORMATION TRANSFER TECHNIQUE IN TEACHING WRITING - Ummi Khaerati Syam; Ismail Sangkala (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2014)
Writing is one of the language skills that plays important role in human communication. It is used to communicate with other people in society and also to express our opinion in writing form. The teaching of writing requires the students to write accurately. Have a good competence in English does not only mean to be fluent speakers of the language, as many people have in mind but in writing as well; a lot of varieties of occupations require skilled people in English both in speaking and writing. There are some factors that influence the students’ ability to write; they are the vocabulary, the interesting topics were given the interest of students in learning writing such as picture, map, graphic, etc and the time to teach writing in English course or inappropriate technique. Among these factors, technique is an important factor that should be given a special attention because by applying a good technique, the students can improve their ability to organize their ideas into a good writing. This research is intended to find out the improvement of the students’ writing ability by using Information Transfer Technique at first semester students’ of Muhammadiyah University of Makassar. The method will use a Pre-Experimental research with the one group pretest and posttest design. The sample is only one class that consisted of 40 students which were selected by using Purposive sampling technique. The data were obtained through writing test.